2021
DOI: 10.3892/ijmm.2021.4853
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR‑101‑3p protects against sepsis‑induced myocardial injury by inhibiting MAPK and NF‑κB pathway activation via the upregulation of DUSP1

Abstract: Numerous studies have found that microRNAs (miRNAs or miRs) are aberrantly expressed when sepsis occurs. The present study aimed to investigate the role of miR-101-3p in sepsis-induced myocardial injury and to elucidate the underlying mechanisms. Models of myocardial injury were established both in vivo and in vitro . The results revealed that miR-101-3p was upregulated in the serum of patients with sepsis-induced cardiomyopathy (SIC) and positively correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Normally, the intestinal epithelium prevents proinflammatory LPS translocation, but circulating LPS levels are elevated in diet-induced obese and diabetic mice (Clemente-Postigo et al, 2019). Research revealed that LPS induced marked cardiac dysfunction, apoptosis, and inflammation in myocardial injury models (Xin et al, 2021). Interestingly, vagal nerve electrical stimulation potently reduces intestinal inflammation by restoring intestinal homeostasis, whereas vagotomy has the reverse effect (Matteoli and Boeckxstaens, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the intestinal epithelium prevents proinflammatory LPS translocation, but circulating LPS levels are elevated in diet-induced obese and diabetic mice (Clemente-Postigo et al, 2019). Research revealed that LPS induced marked cardiac dysfunction, apoptosis, and inflammation in myocardial injury models (Xin et al, 2021). Interestingly, vagal nerve electrical stimulation potently reduces intestinal inflammation by restoring intestinal homeostasis, whereas vagotomy has the reverse effect (Matteoli and Boeckxstaens, 2013).…”
Section: Discussionmentioning
confidence: 99%
“… 34 Evidence suggests that miR-101-3p up-regulates and inhibits its specific target dual specificity phosphatase-1 (DUSP1) in LPS-induced myocardial injury mice, further activates MAPK and NF-κB signaling pathways to induce apoptosis. 35 It is verified properly that activation of the MAPK pathway is demonstrated by its phosphorylation. 36 Then, the TNF-α/P38-MAPK/caspase-3 signaling pathway was activated in SIMI to induce apoptosis of cardiomyocytes, which can stand the test of experiment.…”
Section: Apoptosis Of Simimentioning
confidence: 74%
“…Recent studies have identified additional miRNAs that may be involved in sepsis-induced cardiomyopathy. The group of Ye et al focused on the role of miR-101-3p [ 99 ]. In this study, both in vivo and in vitro models of myocardial damage were established.…”
Section: Resultsmentioning
confidence: 99%